Profile of clinic nutricionist and its performance in doctor´s offices in the City of Fortaleza - Ceara - Maria Soraia Pinto; Juliana de Araújo Silva (Universidade de Fortaleza, 2012)
Objective: To characterize the role of nutritionist in private offices in a municipality. Methods: Cross sectional study with a quantitative approach, and population composed of 45 nutritionists who attended clinics in the city of Fortaleza - CE, Brazil. We used aquestionnaire consisting of sociodemographic data, academic standing, professional activities and information. The data were organized by the Statistical Package for Social Sciences - SPSS, version 15. Results: The sample revealed a predominance of women - 43(95.6%), with a mean age of 21 to 30 years - 15 (33.3%), married - 30 (66.7%), Catholic - 34(75.6%), white - 32 (71.1%) and natural state of Ceara - 34 (75.4%). Of the total sample, 40 (88.9%) graduated in public universities, 24 (53.3%) had more than 10 years since graduation, and 40 (88.9%) had some kind of graduate. There was a positive associationbetween duration of graduate and professional income. The quest for slimming / weight loss with 40 (91.1%) was considered the most cited reason for consultation with a nutritionist.The "inadequate remuneration" was reported by 23 (51.1%) of respondents as the mainnegative factor of the profession. Conclusions: The results showed a young professional, seeking updates on the area where it operates and that aims professional autonomy. The article opens promising perspectives for the potential contributions to improving the qualityof information about the profile of these professionals.